Expression of Anger and Ill Health in Two Cultures: An Examination of Inflammation and Cardiovascular Risk. (February 2015) - Kitayama, Shinobu; Park, Jiyoung; Boylan, Jennifer Morozink; Miyamoto, Yuri; Levine, Cynthia S.; Markus, Hazel Rose; Karasawa, Mayumi; Coe, Christopher L.; Kawakami, Norito; Love, Gayle D.; Ryff, Carol D.
Expression of anger is associated with biological health risk (BHR) in Western cultures. However, recent evidence documenting culturally divergent functions of the expression of anger suggests that its link with BHR may be moderated by culture. To test this prediction, we examined large probability samples of both Japanese and Americans using multiple measures of BHR, including pro-inflammatory markers (interleukin-6 and C-reactive protein) and indices of cardiovascular malfunction (systolic blood pressure and ratio of total to HDL cholesterol). We found that the link between greater expression of anger and increased BHR was robust for Americans. As predicted, however, this association was diametrically reversed for Japanese, among whom greater expression of anger predicted reduced BHR. These patterns were unique to the expressive facet of anger and remained after we controlled for age, gender, health status, health behaviors, social status, and reported experience of negative emotions. Implications for sociocultural modulation of bio-physiological responses are discussed.